Advances in photovoltaics, part 4 (Semiconductors and semimetals, 2015)
Advances in Photovoltaics: Part Four provides valuable information on the challenges faced during the transformation of our energy supply system to more efficient, renewable energies. The volume discusses the topic from a global perspective, presenting the latest information on photovoltaics, a cornerstone technology. It covers all aspects of this important semiconductor technology, reflecting on the tremendous and dynamic advances that have been made on this topic since 1975, when the first book on solar cells-written by Harold J. Hovel of IBM-was published as volume 11 in the now famous series on Semiconductors and Semimetals. Readers will gain a behind the scenes look at the continuous and rapid scientific development that leads to the necessary price and cost reductions in global industrial mass-production